Low Energy Adaptive Clustering Hierarchy (LEACH) Protocol for Extending the Lifetime of the Wireless Sensor Network - R, Ghosh; S, Mohanty; S, Pramanik (International Journal of Computer Sciences and Engineering, 2019)
Wireless Sensor Network (WSN) is demanding and very appealing technology useful for different applications. WSNs consist of wirelessly interconnected sensor nodes (SNs) which can assemble, distribute and process information in a range of application regions. Power utilization in WSN is a key difficulty. Some of the usages comprise landslide detection, glacial monitoring, wildlife tracking, health care, military applications, environmental monitoring and a large number of applications to robotics and projects on “internet of things”. Our paper will illustrate the primary characteristics of WSN followed by power consumption protocol LEACH. Here we have carried out the comparative performance analysis of power consumption protocol LEACH at different energy levels and multi-path factors.